2010
DOI: 10.4314/njps.v21i1-2.53971
|View full text |Cite
|
Sign up to set email alerts
|

Safety and hypoglycaemic properties of aqueous leaf extract of <i>Ocimum gratissimum</i> in streptozotocin induced diabetic rats.

Abstract: Summary:The claim by Nigerian traditional herbal medicine practitioners that Ocimum gratissimum leaves have antidiabetic properties was investigated. Diabetes mellitus was induced with streptozotocin and graded doses of the aqueous leaf extract were administered orally to the experimentally diabetic rats for 28 days. Administration of the aqueous leaf extract caused a statistically significant reduction in plasma glucose level in streptozotocin induced diabetic rats. The extract appeared nontoxic as evidenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 9 publications
(9 reference statements)
7
41
0
1
Order By: Relevance
“…The lowering effect of blood sugar levels by Ocimum lamiifolium in the same manner regardless of the dosage might suggest that the extract may have been absorbed in the cell system through active transport where a particular concentration saturation of the extract occurred resulting to the rest of extract being excreted [16]. Similar results have been reported on the hypoglycemic activity of plant extracts of L. wightiana and L. camara Linn [17,18], Artemisia herba [19] Colocynthis citrullus [20] and Ocimum gratissimum [21,22].…”
Section: Discussionsupporting
confidence: 74%
“…The lowering effect of blood sugar levels by Ocimum lamiifolium in the same manner regardless of the dosage might suggest that the extract may have been absorbed in the cell system through active transport where a particular concentration saturation of the extract occurred resulting to the rest of extract being excreted [16]. Similar results have been reported on the hypoglycemic activity of plant extracts of L. wightiana and L. camara Linn [17,18], Artemisia herba [19] Colocynthis citrullus [20] and Ocimum gratissimum [21,22].…”
Section: Discussionsupporting
confidence: 74%
“…Hypoglycemic and antidiabetic activity in rats have also been studied. Egesie and his colleagues concluded that the plant was an effective antidiabetic agent [21]. Because the administration of graded doses of the aqueous leaf extract produced a statistically significant decrease (P < 0.05) in serum glucose concentration when compared with diabetic control rats and normal control rats they also reported that twenty eight day administration of the extract to non diabetic rats did not produce any significant difference in the plasma glucose concentration of non diabetic extract treated rats compared with control [21].…”
Section: Introductionmentioning
confidence: 91%
“…A number of studies in the past have been conducted to investigate the hypoglycaemic or possible antidiabetic effects of Ocimum gratissimum [9,21,22]. This study investigated the effects of Ocimum gratissimum on blood glucose levels in the diabetic state using the ethanolic extract of the leaves which contains a higher concentration of secondary constituents that are present in both extracts (ethanolic and aqeous ), and has lipids and eugenol which are absent in the aqueous extract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations